The Implementation of Law Number 6/2014 on Villages in the Village Government in Sleman Regency - Pravita, Vina Dini; Handoko, V. Rudy; Indartuti, Endang (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
Villages in Indonesia are governed by a village government, as defined in Article 2 of Law No. 6/2014, which states that the village government handles local affairs within Indonesia’s government structure. Villages are required to perform government tasks following legal provisions, including planning, implementation, administration, supervision, and evaluation. While villages are not part of the territorial hierarchy in the decentralization system, they have the authority to create village regulations, which are considered part of the legal framework in Indonesia. However, villages face constraints due to higher-level regulations that limit their autonomy and are often seen as lacking the capacity to manage their own governance. The research focuses on the mismatch between village policies and the conditions in Sleman Regency. It addresses issues such as the impact of Law No. 6/2014 on village independence and public services, as well as effective public service models in the region. Using qualitative research with an analytical descriptive approach, the study finds that the policy implementation has not been optimal. One major issue is the lack of flexibility in the policy content to meet the needs of the village government, leading to obstacles in providing efficient public services at the village level. The study identifies key findings, including limited village independence due to supra-village regulations, resource constraints, and communication barriers between policy makers and implementers. It highlights positive outcomes such as improved administrative order and innovation in revenue generation by village governments. The research concludes with recommendations for enhancing flexibility in policy content, strengthening resources, and fostering innovation to better align public services with community needs.